Faktor-Faktor Yang Mempengaruhi Discretionary Loan Loss Provisions Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Sofia Prima Dewi; Eveline Eveline (Jurnal Manajemen, 2017)
The purpose of this study was to obtain empirical evidence about the effect of earnings before tax and provisions, the quality of voluntary disclosure, needs for external financing, other alternatives to earnings management, and firm size to discretionary loan loss provisions in banking companies listed in Indonesia Stock Exchange. The samples used were 26 banking companies listed in Indonesia Stock Exchange during 2011-2013. Data analysis was performed with the aid of a software program Statistical Product and Service Solutions (SPSS) for Windows version 20. The results showed that earnings before tax and provisions have an influence on discretionary loan loss provisions, while the quality of voluntary disclosure, needs for external financing, other alternatives to earnings management, and firm size does not have any influence on discretionary loan loss provisions.